The Effectiveness of the RADEC Learning Model Assisted by Digital Comics Media on Students Learning Outcomes and Interest in Learning - Wandani, Roni Wahyu; Sopandi, Wahyu; Sujana, Atep; Rosmiati, Ika (International Conference on Elementary Education, 2022)
This research aims to determine the effectiveness of learning science on science learning through the application of the RADEC (Read, Answer, Discuss, Explain and Create) model with the aid of digital comic media. This type of research is experimental research with a pre-experimental design and the form of research is a one-shot case study. The experimental unit in this study was 20 students of class VA SDN 264 Griya Bumi Antapani as a test class for the application of the RADEC model with the help of digital comic media which was selected using a random sampling technique. The results showed that the descriptive analysis obtained the following results: (1) The implementation of science learning was 3.87 which was in the very good category. (2) The average student learning outcome in science is 78.37 (3) The average percentage of student activity is reaching a percentage of 88% (4) The student response questionnaire shows that most students respond with a percentage of 92.5%. The results of the inferential analysis show that the students' science learning outcomes after the application of the RADEC model assisted by digital comic media are more than the Standard Minimum of Completeness or H1 scores accepted.